Longitudinal Profiles and Predictors of Physical Activity in Cancer Survivors Post-Exercise Intervention: A 5-Year Follow-Up of the Phys-Can RCT - Anna-Karin Ax PhD; Andreas Stenling PhD; Sveinung Berntsen PhD; Sussanne Börjeson PhD; Karin Nordin PhD; Ingrid Demmelmaier PhD; Anne-Sophie Mazzoni PhD (Integrative Cancer Therapies)
Background: Regular physical activity improves health outcomes in cancer survivors; however, maintaining recommended levels of moderate-to-vigorous intensity physical activity (MVPA) post-treatment is challenging, even for those participating in exercise intervention studies. Understanding long-term MVPA patterns and predictors can guide strategies to promote sustained physical activity in this population. We aimed to describe objectively measured MVPA-profiles over 5 years in cancer survivors who participated in a 6-month exercise intervention during cancer treatment, and to identify baseline predictors of profile belonging. Methods: Data were derived from the multicenter randomized controlled trial Phys-Can, including participants with breast, colorectal or prostate cancer. Objective measures of MVPA were conducted at baseline, post-intervention, and at 1-, 2-, and 5-year follow-ups. Longitudinal latent profile analysis was used to identify MVPA profiles, and multinomial logistic regression to examine potential baseline predictors of profile belonging. Results: Among 556 participants, 4 longitudinal MVPA profiles were identified: Low and stable (18.0%), Medium and stable (40.8%), High and decreasing (28.4%), and Very high and stable (12.8%). Compared to the Very high and stable MVPA profile, participants in the Low and stable MVPA profile were more likely to be women (OR = 20.64) or have higher BMI (OR = 1.41) or lower cardiorespiratory fitness (OR = 0.69) at baseline. Conclusion: Cancer survivors who are women or have a higher BMI and/or low cardiorespiratory fitness prior to cancer treatment are at greater risk of maintaining low MVPA levels over time. These groups may require targeted support to enhance and sustain physical activity during survivorship.